2022
DOI: 10.3390/jcm11185334
|View full text |Cite
|
Sign up to set email alerts
|

Microballoon Interventions for Liver Tumors: Review of Literature and Future Perspectives

Abstract: Background: Microballoon interventions (MBIs) have been proposed as useful tools to improve the efficacy of locoregional liver treatments. The aim of this systematic review was to summarize the existing evidence on procedural characteristics, safety, and efficacy of MBIs. Methods: PubMed and Cochrane Central Register of Controlled Trials were queried for original research articles evaluating MBIs in patients with liver malignancies from 2012 to August 2022. Search terms employed were liver malignancies, hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To date, the only reported complication directly related to microballoon use has been vascular dilatation at the balloon inflation site. In all reported cases, this event was asymptomatic and was revealed during routine follow-up with contrast-enhanced CT and required no further treatment [7] .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…To date, the only reported complication directly related to microballoon use has been vascular dilatation at the balloon inflation site. In all reported cases, this event was asymptomatic and was revealed during routine follow-up with contrast-enhanced CT and required no further treatment [7] .…”
Section: Discussionmentioning
confidence: 85%
“…Balloon microcatheter intervention had been described in liver chemoembolization for Hepatocellular Carcinoma [7 , 8] . Reported advantages of this technique are reversal of the flow of collateral arteries, reduction in the number of superselective catheterizations, and improvement of results on larger nodules in a single session.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding safety, no studies have reported a significant difference in the rate of complications between procedures performed with and without balloon occlusion [15][16][17][18][19][20][21]. B-TACE has been demonstrated to be safe, with an adverse event rate equivalent to that of C-TACE.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon-occluded transcatheter arterial chemoembolization (B-TACE), in which a microballoon catheter is used to temporarily occlude the tumor feeding artery, was introduced to increase CR rates [13,14]. Although no definitive indications for B-TACE have been established to date, several studies have reported that initial tumor responses are better among patients with HCC who undergo B-TACE than other TACE techniques, including conventional TACE (C-TACE) and drug-eluting bead TACE [15][16][17][18][19][20][21]. However, assessing the quality of CR in terms of the therapeutic outcomes of B-TACE is necessary because the evaluation of LR may provide more detailed information on the ability of the B-TACE to result in a local cure.…”
Section: Introductionmentioning
confidence: 99%